Reliability assessment of ultrasound muscle echogenicity in patients with rheumatic diseases: Results of a multicenter international web-based study - Di Matteo, Andrea; Moscioni, Erica; Lommano, Maria Giovanna; Cipolletta, Edoardo; Smerilli, Gianluca; Farah, Sonia; Airoldi, Carla; Aydin, Sibel Zehra; Becciolini, Andrea; Bonfiglioli, Karina; Carotti, Marina; Carrara, Greta; et al. (Frontiers in Medicine, 2023)
Objectives To investigate the inter/intra-reliability of ultrasound (US) muscle echogenicity in patients with rheumatic diseases. Methods Forty-two rheumatologists and 2 radiologists from 13 countries were asked to assess US muscle echogenicity of quadriceps muscle in 80 static images and 20 clips from 64 patients with different rheumatic diseases and 8 healthy subjects. Two visual scales were evaluated, a visual semi-quantitative scale (0-3) and a continuous quantitative measurement (‘VAS echogenicity’, 0-100). The same assessment was repeated to calculate intra-observer reliability. US muscle echogenicity was also calculated by an independent research assistant using a software for the analysis of scientific images (ImageJ). Inter and intra reliabilities were assessed by means of prevalence-adjusted bias-adjusted Kappa (PABAK), intraclass correlation coefficient (ICC) and correlations through Kendall's Tau and Pearson’s Rho coefficients. Results The semi-quantitative scale showed a moderate inter-reliability [PABAK=0.58 (0.57-0.59)] and a substantial intra-reliability [PABAK=0.71 (0.68-0.73)]. The lowest inter and intra-reliability results were obtained for the intermediate grades (i.e., grade 1 and 2) of the semi-quantitative scale. ‘VAS echogenicity’ showed a high reliability both in the inter-observer [ICC=0.80 (0.75-0.85)] and intra-observer [ICC=0.88 (0.88-0.89)] evaluations. A substantial association was found between the participants assessment of the semi-quantitative scale and ‘VAS echogenicity’ [ICC=0.52 (0.50-0.54)]. The correlation between these two visual scales and ImageJ analysis was high (tau=0.76 and rho=0.89, respectively). Conclusions The results of this large, multicentre study highlighted the overall good inter and intra-reliability of the US assessment of muscle echogenicity in patients with different rheumatic disease.